Percolation like transitions in phase separated manganites La0.5Ca0.5Mn1-xAlxO3-δ. Issue 15 (15th October 2019) - Shang, C.; Xia, Z.C.; Zhai, X.Z.; Liu, D.W.; Wang, Y.Q.
Abstract: We show that the replacement of Mn with Al strongly affects the magnetization and electrical transport behaviors in La0.5 Ca0.5 Mn1- x Al x O3- δ ( x = 0, 0.05, 0.07 and 0.09). Nonmagnetic Al 3+ ions substitution at Mn sites dilutes Mn 3+ -O 2- -Mn 4+ network, thus suppresses the ferromagnetic metallic state in La0.5 Ca0.5 MnO3- δ and causes a phase separation phenomenon, in which ferromagnetic phase coexists with antiferromagnetic charge ordered phase at low temperatures. With applying sufficiently high magnetic field, step-like metamagnetic transitions were observed in x = 0.05–0.09 systems below helium temperature, in which the antiferromagnetic charge ordered phase collapsed into ferromagnetic phase. Corresponding to the sharp step-like metamagnetic transitions, the resistivity decreases dramatically with increasing magnetic field, exhibiting a percolative insulator-metal transition. The variation of temperature and magnetic field changes the relative fractions of ferromagnetic and charge ordering phases, and percolative insulator-metal transition occurs due to the development of percolation paths between the growing FM domains.